The Political Symbols and the Exercise of Traditional Authority in Dagbon Chieftaincy - Shamhuna, Abdul Aziz (LECTURES: Journal of Islamic and Education Studies, 2025)
This paper investigates the influence of political symbols on the dynamics of traditional authority within the Dagbon chieftaincy, focusing on how these symbols interact with cultural representation and existing power structures. By addressing the significance of political symbols in legitimizing authority and shaping governance practices, this research employs qualitative methodologies, including ethnographic interviews, archival records, and participant observations, to uncover a refined understanding of their role in contemporary Dagbon politics. Key findings reveal that symbols such as regalia, rituals, and public displays not only reinforce traditional leadership but also serve as instruments for negotiating power within modern political frameworks. Additionally, these symbols significantly impact the community’s perception of governance and influence healthcare delivery by aligning health initiatives with cultural values, thereby enhancing community participation and compliance. The implications of this study extend to the field of healthcare, emphasizing the necessity of culturally sensitive governance structures that incorporate traditional authority to improve health outcomes. By highlighting the intersection of political symbolism and healthcare practices within traditional settings, this research contributes to the broader discourse on the role of cultural competency in health governance, advocating for interdisciplinary approaches that bridge traditional authority and contemporary health policy frameworks.